Perceptions and reported practices of pregnant women and mothers of children under two years of age regarding antibiotic use and resistance in Vientiane province, Lao PDR: a qualitative study - Vanphanom Sychareun; Paphatsone Phounsavath; Amphoy Sihavong; Sengchanh Kounnavong; Kongmany Chaleunvong; Anna Machowska; Bounxou Keohavong; Mayfong Mayxay; Jaran Eriksen; Claudia Hanson; Manivanh Vongsouvath; Annelie Brauner; et al. (BMC, 2022)
Abstract Background Understanding pregnant women and mothers' perceptions towards antibiotic use and resistance is essential for appropriate antibiotic use and limiting antibiotic resistance. This study aimed to explore perceptions and reported practices of pregnant women and mothers with children under two years of age regarding correct antibiotic use and antibiotic resistance in Vientiane Province, Lao PDR. Methods The study employed an exploratory qualitative research design using focus groups discussions (FGDs). Participants were purposively selected based on: being pregnant at third trimester and attending antenatal care and mothers with children under two years of age, attending the health facility for postpartum visit /vaccinations. Six focus group discussions were conducted in September 2019 with a total of 55 women. The FGDs were transcribed verbatim, data were analyzed first by coding then categorizing the data as we looked for patterns and themes by using the qualitative content analysis. Results Most participants had some understanding of antibiotics but wrongly believed antibiotics can be used to treat viral disease. Over half of the participants had heard the term "antibiotic resistance", but often believed it was their bodies, not the bacteria that developed antibiotic resistance. During pregnancy and for their infants, women preferred to use antibiotics only when prescribed by a doctor. Outside of pregnancy however, consuming antibiotics without a prescription was commonly reported. Participants wanted more information about the indications for antibiotic use and antibiotic resistance. Conclusions More effort is required to increase the level of understanding, and practice of mothers to promote optimal antibiotic use. Mothers' desire to learn more, and their fundamental concern for their children, can be used to promote appropriate antibiotic use. Awareness raising should be complemented by efforts to address other determinants of inappropriate antibiotic use, including educating healthcare workers, and pharmacists and addressing health service determinants that contribute to inappropriate antibiotic use.